Bioactive Molecules from the Exoskeleton of Procambarus clarkii: Reducing Capacity, Radical Scavenger, and Antitumor and Anti-Inflammatory Activities - Francesco Longo; Francesca Di Gaudio; Alessandro Attanzio; Laura Marretta; Claudio Luparello; Serena Indelicato; David Bongiorno; Giampaolo Barone; Luisa Tesoriere; Ilenia Concetta Giardina; Giulia Abruscato; Manuela Perlotti; et al. (Biomolecules, 2024)
This study evaluates, for the first time, the reducing capacity, radical scavenger activity, and in vitro antitumor and anti-inflammatory effects of chitosan, astaxanthin, and bio-phenols extracted from the exoskeleton of Sicilian Procambarus clarkii, the most widespread species of invasive crayfish in the Mediterranean region. Among the extracted compounds, astaxanthin exhibited the highest antioxidant activity in all assays. Chitosan and polyphenols demonstrated reducing and radical scavenging activity; chitosan showed significant ferric ion reducing capacity in the FRAP test, while bio-phenolic compounds displayed notable radical scavenging activity in the DPPH and ABTS assays. Both astaxanthin and polyphenols showed dose-dependent cytotoxicity on two different cancer cell lines, with IC50 values of 1.45 µg/mL (phenolic extract) and 4.28 µg/mL (astaxanthin extract) for HepG2 cells and 2.45 µg/mL (phenolic extract) and 4.57 µg/mL (astaxanthin extract) for CaCo-2 cells. The bio-phenolic extract also showed potential anti-inflammatory effects in vitro by inhibiting nitric oxide production in inflamed RAW 264.7 macrophages, reducing the treated/control NO ratio to 77% and 74% at concentrations of 1.25 and 1.5 μg/mL, respectively. These results suggest that P. clarkii exoskeletons could be a valuable source of bioactive molecules for biomedical, pharmaceutical, and nutraceutical application while contributing to the sustainable management of this invasive species.